2016
DOI: 10.3382/ps/pev368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation of phytogenic feed additives (powdered vs. encapsulated) on performance and nutrient digestibility in broiler chickens

Abstract: Inclusion of phytogenic feed additives (PFA) in feed may enhance performance of broilers. Levels of essential oils in powdered form (characterized by menthol and anethole) at 150 mg/kg (P-150) and matrix-encapsulated form (characterized by carvacrol, thymol, and limonene) at 100 mg/kg (ME-100) were supplemented in diet to investigate their effect on performance (trial 1) and apparent ileal digestibility (AID) of nutrients (trial 2) in broilers. A total of 480 1-day-old broilers (Cobb 500) were used in trial 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 30 publications
3
66
0
2
Order By: Relevance
“…This study was to investigate the pathways in the somatic growth and nutritional physiology of Nile tilapia that could be affected by turmeric, rosemary and thyme additive. The three phytogenic compounds had been shown to be a promote growth in monogastric animals (Hafeez et al, 2016), as it confirmed herein with Nile tilapia. Given that it remained unclear which pathways are involved in promoting growth.…”
Section: Immune Responsesupporting
confidence: 79%
“…This study was to investigate the pathways in the somatic growth and nutritional physiology of Nile tilapia that could be affected by turmeric, rosemary and thyme additive. The three phytogenic compounds had been shown to be a promote growth in monogastric animals (Hafeez et al, 2016), as it confirmed herein with Nile tilapia. Given that it remained unclear which pathways are involved in promoting growth.…”
Section: Immune Responsesupporting
confidence: 79%
“…Bioactive compounds are widely used as zootechnical additives to increase animals weight gain and performance. A general positive effect was shown for feed intake, weight gain, and feed conversion rate in piglets, sows, and poultry, while inconsistent data were registered for apparent digestibility in piglets (Franz et al, 2010;Christaki et al, 2012;Zeng et al, 2015) possibly due to improved secretion of digestive enzymes and bile secretion (Hafeez et al, 2015). A positive effect on gut microbiota in monogastric animals was also reported by several authors (Tiihonen et al, 2010;Bento et al, 2013).…”
Section: Feed Applicationsmentioning
confidence: 65%
“…Study conducted by Toghyani et al (2010) reported that broilers receiving 5 g.kg -1 thyme had a significantly higher body weight at day 42 of age, while a report published by Kamali Sangani et al (2014) claimed the opposite by demonstrating that no significant effect was recorded. In the experiment Hafeez et al (2016) were body weight of birds at day 42 and overall body weight gain from day 1 to day 42 higher in treatment by carvacrol, thymol, and limonene than birds in control treatment.…”
Section: Resultsmentioning
confidence: 84%